2017
DOI: 10.1101/083428
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exonic Mosaic Mutations Contribute Risk for Autism Spectrum Disorder

Abstract: Genetic risk factors for autism spectrum disorder (ASD) have yet to be fully elucidated. Postzygotic mosaic mutations (PMMs) have been implicated in several neurodevelopmental disorders and overgrowth syndromes. By leveraging whole-exome sequencing data on a large family-based ASD cohort, the Simons Simplex Collection, we systematically evaluated the potential role of PMMs in autism risk. Initial re-evaluation of published single-nucleotide variant (SNV) de novo mutations showed evidence consistent with putati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 79 publications
1
24
0
Order By: Relevance
“…A similar finding was reported in a cancer study . In addition, a recent study analyzing postzygotic mosaic mutations in ASD (2264 families: 1698 quads and 566 trios) reported enrichment of near‐splice site synonymous mosaic mutations in ASD . In this study, the authors also reanalyzed high‐confidence germline synonymous DNM and confirmed that these DNM in ASD are significantly closer to splice sites than in controls, indicating that both germline and postzygotic mosaic synonymous mutations are enriched in near‐splice site regions in ASD.…”
Section: Rapidly Expanding Knowledge On Functional Non‐coding Elementssupporting
confidence: 87%
“…A similar finding was reported in a cancer study . In addition, a recent study analyzing postzygotic mosaic mutations in ASD (2264 families: 1698 quads and 566 trios) reported enrichment of near‐splice site synonymous mosaic mutations in ASD . In this study, the authors also reanalyzed high‐confidence germline synonymous DNM and confirmed that these DNM in ASD are significantly closer to splice sites than in controls, indicating that both germline and postzygotic mosaic synonymous mutations are enriched in near‐splice site regions in ASD.…”
Section: Rapidly Expanding Knowledge On Functional Non‐coding Elementssupporting
confidence: 87%
“…Both representations describe the same resulting genotype. The other three papers report just one of the contiguous SNVs each [Krupp et al, ]: C‐ > A; [Ji et al, ]; and [Satterstrom et al, ]: C‐>G). This complex variant can also be viewed directly in VariCarta at varicarta.msl.ubc.ca/variant?chr=5&start=134059281&stop=134059281.…”
Section: Resultsmentioning
confidence: 99%
“…Pathogenic variants in CHD2 have been identified in patient cohorts diagnosed with other neurodevelopmental disorders, including autism spectrum disorder, 1,4,6,13,14 intellectual disability, 15 developmental delay, 16,17 microcephalus, 6 developmental malformation, 18,19 and facial abnormalities. 1,10,18,20 Not all patients have seizures.…”
Section: Discussionmentioning
confidence: 99%